Pengaruh bone graft dan splitting osteotomy terhadap perkembangan akar gigi molar ketiga immature yang ditransplantasi The effect of bone graft and splitting osteotomy on development of the root of transplanted immature third molar - Irma Drismayanti; Sariatun T; Surijana Mappangara; Muh. Ruslin (DiscoverSys Inc., 2011)
One of the basic requirements for succesfull transplantation is an adequate size of recipient site with sufficientalveolar support. If the transplantation is performed into a fresh extraction site, the recipient site can easily beadjusted to the transplantation. However, the situation is different in patient with premolar aplasia or early molarloss with marked atrophy of the alveolar process, need additional surgical procedures like bone autograft orsplitting osteotomy of the alveolar process. This paper discussed the effect of bone autograft and splitting osteotomyon root development of transplanted immature third molars. The conclusion is these additional surgical prosedureshad a negative effect on the pulpal and periodontal condition of transplantated immature third molars. This may berelated to revascularization disturbances of pulp due to nutrient insufficiency of the recipient site.